Student pedagogical partnerships to advance inclusive teaching during the COVID-19 pandemic - Addy, Tracie Marcella; Berkove, Ethan; Borzone, Manuela; Butler, Mike; Cham, Fatimata; deSaussure, Annie; Exarhos, Annemarie; Mancuso, Mark; Rizk, Monica; Rossmann, Tobias; et al. (International Journal for Students as Partners, 2022)
The current health crisis brought about by the COVID-19 pandemic not only had a global impact, it also exacerbated the inequalities experienced by students of diverse backgrounds in the United States. Implementing inclusive and anti-racist pedagogical practices has gained a heightened and overdue sense of urgency, especially during the period of emergency remote teaching. At Lafayette College, a small liberal arts college in Pennsylvania, USA, the Inclusive Instructors Academy is a semester-long program aimed at supporting faculty from all disciplines to develop and incorporate inclusive practices that promote equity and belonging in their teaching. A critical aspect of the Inclusive Instructors Academy is its employment of student fellows under the Student-as-Partners model. The student fellows who participated in Fall 2020 and Spring 2021 provided feedback to their faculty partners on inclusive teaching approaches. This case study highlights how student-faculty partnerships can be a highly effective strategy for fostering more socially just learning environments.